Evaluation of concrete strength and permeability with time - Tackett, Paul M. (Kansas State University, 2013)
The relationship between in-place concrete strength and permeability with concrete cylinder strength and permeability with time is of interest - especially when supplementary cementitious materials (SCMs) are used. A joint research project between The University of Kansas was undergone to quantify these relationships. The permeability of concrete is directly tied to its ability to mitigate certain failure mechanisms such as corrosion and sulfate attack. The three concrete mixtures being tested by Kansas State University (KSU) vary in cementitious content as follows: (1) 100% ordinary portland cement (OPC), (2) 25% Class F fly ash (F-ash) and 75% OPC, (3) 25% Class C fly ash (C-Ash) and 75% OPC. The mixtures were also placed in three different seasons to present differing curing environmental effects. The summer slabs were cast during July and August. The fall slabs were cast in October and November. The final set of slabs were cast in March and April. Three sets of concrete specimens (lab cured, field cured and in-situ core specimens) were tested at 28, 56, 90, 180, and 360 days for strength and permeability properties. The permeability performance tests being utilized are ASTM C1202 and ASTM C642. The results have shown very desirable permeability and strength data for the mixes using blended fly ash cements. The F-ash exhibited the best high early strength and low permeability data for the summer placement season and slower strength and permeability performance at cold weather. The C-ash performed the best overall for all seasons and had the least environmental effects. The OPC performed the worst in regards to permeability and did not reach as high long term strength.
Keywords: Concrete; Permeability containing; Fly Ash SCMs; Civil Engineering (0543)